RDF database systems : triples storage and SPARQL query processing - Curé, Olivier (Morgan Kaufmann, 2015)
"If you have this book in your hands, we guess you are interested in database management systems in general and more precisely those handling Resource Description Framework (RDF) as a data representation model. We believe it is the right time to study such systems because they are getting more and more attention in industry with communities of Web developers and information technology (IT) experts who are designing innovative applications, in universities and engineering schools with introductory and advanced courses, and in both academia and industry research to design and implement novel approaches to manage large RDF data sets. We can identify several reasons that are motivating this enthusiasm"--